ANALISIS BIBLIOMETRIK PERKEMBANGAN MUTAKHIR DALAM STUDI ANISOTROPI SEISMIK (2017 -2022): BIBLIOMETRIC ANALYSIS OF RECENT DEVELOPMENT IN THE SEISMIC ANISOTROPY STUDIES (2017 -2022) - Yuda, Himmes Fitra; Ronoatmojo, Imam Setaiji; Burhannudinnur, Muhammad; Nuryana, Suherman Dwi (Universitas Trisakti, 2024)
The development of seismic anisotropy needs to be studied systematically hence research could be focused on the latest scientific knowledge, therefore a bibliometric analysis is needed as a measurement of citation strength in the form of mapping